2006
DOI: 10.1378/chest.130.3.863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rabbit Tracheal Inflammation Using Optical Coherence Tomography

Abstract: This study suggests that OCT is a potentially valuable imaging modality that is capable of evaluating superficial airway pathology with high-resolution in vivo images. Numerous applications of OCT can be envisioned in the realm of pulmonary medicine and thoracic surgery that may substantially increase the precision and accuracy of current bronchoscopic diagnostic and surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The airway wall segmentation and measurement methods have been described in detail (31); similar software-based airway tissue measurement has been validated in previous OCT studies (12)(13)(14)(15)(16)(17). A single optimal data set from each LR-OCT case was selected based on signal-to-noise ratio, clarity of tissue contours, and soft tissue substructural resolution.…”
Section: Image Segmentation and Micrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The airway wall segmentation and measurement methods have been described in detail (31); similar software-based airway tissue measurement has been validated in previous OCT studies (12)(13)(14)(15)(16)(17). A single optimal data set from each LR-OCT case was selected based on signal-to-noise ratio, clarity of tissue contours, and soft tissue substructural resolution.…”
Section: Image Segmentation and Micrometrymentioning
confidence: 99%
“…OCT evaluation and measurement of airway wall microanatomy has been validated with comparative computed ORIGINAL ARTICLE tomography (12) and histology (13)(14)(15)(16)(17). Previous reports describe OCT imaging of postintubation subglottic injury in ex vivo animal models (17,18) and intubated neonates (19).…”
mentioning
confidence: 99%
“…The movements should be smooth and coordinated in order not to compromise the quality of the image. The similarity between OCT images and those produced evaluation of smoke-induced airway injury, (2) evaluation of anastomosis and small airways in lung transplantation, performance of endobronchial biopsies, (21) and measurement of tracheobronchial stenosis, (20) as well as evaluation of normal microanatomy and small airway and smooth muscle thickening in asthma patients, (22) COPD patients, (23) cystic fibrosis patients, and smokers, (24,25) together with pre-and post-bronchial thermoplasty evaluation. (26) In addition, OCT can aid in determining the size of the bronchi in the endoscopic treatment of emphysema with one-way valves.…”
Section: Discussionmentioning
confidence: 92%
“…Their study demonstrated the diagnostic sensitivity of FD-OCT in identifying and characterizing tissue planes within the subglottic mucosa. Additional studies comparing OCT and histology demonstrate the validity of OCT-based measurements of airway mucosal thickness in animal models [25, 26] and human tissue [27]. …”
Section: Discussionmentioning
confidence: 99%